O direito fundamental à motivação das decisões judiciais e a exigência de eficiência nas dimensões interpretativa, endoprocessual e gerencial - Dall'Alba, Felipe Camilo (2022)
In order to fulfill its constitutional purpose, the reasoning of the sentence must be interpreted according to efficiency. The method used in the present investigation was hypothetical-deductive, and the types of research were qualitative, bibliographical and case law. The present work begins with the history of the legal reasoning. Its presence is perceived in most of legal systems of the Middle Ages, such as Italian, Portuguese, and French, and its consolidation occurred in the French Revolution. The connection between Portugal and Brazil in the topic is proximate, as it was provided in the Ordinations. Nowadays, o principle of legal reasoning is present in the Constitution and in the Civil Procedure Code. It must be structured in such a way that reasoning/justification is as most rational as possible. In the pursuit of the efficiency of reasoning, it is relevant to know the law of other nations, because the foreign experience points in the direction that, in those countries (Italy, France, Portugal, and England), clarity and concision of legal decisions matter. Efficiency, to fulfill its task, must be analyzed considering interpretational, managerial and endoprocedural views, as they are sides of the same coin. To conclude, the constant dialogue between efficiency and reasoning and the rights to legal counsel, publicity, reasonable time of proceedings, legal certainty and to an impartial judge allows that reasoning must be clear and concise and that judges do not need to analyze every single argument made by the parts.